STRATEGI PEMANFAATAN E-LEARNING DALAM MENGATASI KETERBATASAN JUMLAH DOSEN - Rahmi Rivalina (Balai Besar Guru Penggerak Jawa Timur, 2017)
The increasing number of students demands an increase in the number of lecturers. The addition of qualified lecturers is not easy. One of the effort to overcome this shortage of lectures, Pamulang University started to apply e-learning. This study aims to find out the e-learning strategy as well as the responses of students and lecturers in the utilization of e-learning. The research method is descriptive one. Data collections were done through an interview, direct observation, questionnaire, and documentation study. Based on the result of data processing, it is known that the strategy of e-learning utilization is done through some stages, such as: preparation of facilities and infrastructure (lecture building, ICT facilities, laboratory facilities, computerization in academic affairs, and e-learning technology), strong leadership policy support, and training and socialization to students and lecturers. Students’ responses to e-learning models have not been optimally yet due to the limitations of socialization, content that has not been packaged interestingly and meaningful, students’ relatively low reading interest, curiosity and low reading interest, curiosity and low student motivation, and not conducive learning climate. Responses of lecturers besides not yet optimally in preparing the communicative and inspirational content, the lecturer is not used in utilizing e-learning technology. Although the implementation of e-learning still has some weaknesses/constraints, but to some extent, the utilization of e-learning has been able to help the shortage of lecturers.AbstrakMeningkatnya jumlah mahasiswa menuntut adanya peningkatan jumlah dosen. Penambahan jumlah dosen yang berkualitas ternyata tidak mudah. Salah satu upaya untuk mengatasi hal tersebut, Universitas Pamulang menerapkan e-learning. Penelitian ini bertujuan untuk untuk mengetahui strategi pembelajaran e-learning dan respon dari mahasiswa maupun dosen dalam pemanfaatan pembelajaran elearning. Metode penelitian adalah deskriptif. Pengumpulan data dilakukan melalui wawancara, pengamatan langsung, kuesioner, studi dokumentasi. Hasil pengolahan data menunjukkan bahwa strategi pemanfaatan e-learning dilakukan melalui tahapan: persiapan sarana dan prasarana (gedung kuliah, fasilitas TIK, laboratorium, komputerisasi di bidang akademik, dan teknologi e-learning), dukungan kebijakan pimpinan yang kuat, serta pelatihan dan sosialisasi kepada mahasiswa dan dosen. Respon mahasiswa terhadap pembelajaran e-learning belum optimal sebagai akibat keterbatasan mensosialisasi, konten yang belum menarik dan bermakna, minat baca rendah, rasa ingin tahu dan motivasi mahasiswa yang rendah, dan iklim yang belum mendukung. Respon dosen disamping belum optimal menyiapkan konten yang komunikatif dan inspirati juga karena belum terbiasa dalam memanfaatkan teknologi e-learning. Sekalipun memiliki beberapa kekurangan/ kelemahan namun pemanfaatan e-learning tersebut sudah dapat membantu mengatasi kekurangan tenaga dosen.